Legal Protection of Public Image Rights Figures against the Use of Deepfakes in Commercial Advertising Based on Artificial Intelligence - Rohit Nur Alfin; F.X. Ary Setiawan; Elin Sudiarti; Joanita Jalianery (Jurnal Impresi Indonesia, 2026)
The rapid advancement of artificial intelligence technology has given rise to deepfake, an audio-visual manipulation technique capable of realistically replicating a person's face, voice, and gestures without their consent. This phenomenon has emerged in Indonesia’s commercial advertising sector, where public figures such as Najwa Shihab, Raffi Ahmad, and Baim Wong have had their likenesses exploited without authorization. This study aims to analyze the legal protection of public figures’ image rights against deepfake use in commercial advertising and to examine the civil compensation mechanisms available under Indonesian law. The research employs a normative legal method with statute and case approaches, analyzing primary and secondary legal materials through systematic and teleological interpretation. The findings reveal a fundamental legal vacuum (rechtvacuum) in Indonesian law. The Copyright Law, Electronic Information and Transactions Law, and Personal Data Protection Law provide only partial and fragmented protection, as none explicitly recognizes image rights or the right of publicity as an independent legal right. Civil redress relies primarily on Article 1365 of the Civil Code concerning unlawful acts, covering both material and immaterial damages, yet it faces significant evidentiary challenges related to digital forensics. This study concludes that comprehensive legal reform is urgently needed, encompassing amendments to existing laws and the enactment of a dedicated artificial intelligence regulation that explicitly protects digital identity rights.